Differential miRNA Profiles Correlate With Disparate Immunity Outcomes Associated With Vaccine Immunization and Chlamydial Infection - Howard, Simone; Richardson, Shakyra; Benyeogor, Ifeyinwa; Omosun, Yusuf; Dye, Kamran; Medhavi, Fnu; Lundy, Stephanie; Adebayo, Olayinka; Igietseme, Joseph U.; Eko, Francis O. (Frontiers in Immunology, 2021)
Vaccine-induced immune responses following immunization with promising Chlamydia vaccines protected experimental animals from Chlamydia-induced upper genital tract pathologies and infertility. In contrast, primary genital infection with live Chlamydia does not protect against these pathologies. We hypothesized that differential miRNA profiles induced in the upper genital tracts (UGT) of mice correlate with the disparate immunity versus pathologic outcomes associated with vaccine immunization and chlamydial infection. Thus, miRNA expression profiles in the UGT of mice after Chlamydia infection (Live EB) and immunization with dendritic cell (DC)-based vaccine (DC vaccine) or VCG-based vaccine (VCG vaccine) were compared using the NanoString nCounter Mouse miRNA assay. Of the 602 miRNAs differentially expressed (DE) in the UGT of immunized and infected mice, we selected 58 with counts >100 and p-values < 0.05 for further analysis. Interestingly, vaccine immunization and Chlamydia infection induced the expression of distinct miRNA profiles with a higher proportion in vaccine-immunized compared to Chlamydia infected mice; DC vaccine (41,) VCG vaccine (23) and Live EB (15). Hierarchical clustering analysis showed notable differences in the uniquely DE miRNAs for each experimental group, with DC vaccine showing the highest number (21 up-regulated, five down-regulated), VCG vaccine (two up-regulated, five down-regulated) and live EB (two up-regulated, four down-regulated). The DC vaccine-immunized group showed the highest number (21 up-regulated and five down-regulated compared to two up-regulated and four down-regulated in the live Chlamydia infected group). Pathway analysis showed that the DE miRNAs target genes that regulate several biological processes and functions associated with immune response and inflammation. These results suggest that the induction of differential miRNA expression plays a significant role in the disparate immunity outcomes associated with Chlamydia infection and vaccination.